Disseminating a patient-centered education bundle to reduce missed doses of pharmacologic venous thromboembolism (VTE) prophylaxis to a community hospital. Issue 1 (February 2021) - Owodunni, Oluwafemi P; Lau, Brandyn D; Shaffer, Dauryne L; McQuigg, Danielle; Samuel, Deborah; Kantsiper, Mindy; Harris, James E; Hobson, Deborah B; Kraus, Peggy S; Webster, Kristen LW; Holzmueller, Christine G; Kia, Mujan Varasteh; et al.
Background: Venous thromboembolism (VTE) is a leading cause of preventable harm in hospitalized patients. However, many doses of prescribed pharmacologic VTE prophylaxis are frequently missed. We investigated the effect of a patient-centered education bundle on missed doses of VTE prophylaxis in a community hospital. Methods: We performed a pre-post analysis examining missed doses of VTE prophylaxis in a community hospital. A real-time alert from the electronic health record system facilitated the delivery of a patient education bundle intervention. We included all patient visits on a single floor where at least 1 dose of VTE prophylaxis was prescribed during pre- (January 1, 2018, - November 31, 2018) and post- (January 1 - June 31, 2019) intervention periods. Outcomes included any missed dose (primary) and reasons for missed doses (refusal, other [secondary]) and were compared between both periods. Results: 1, 614 patient visits were included. The proportion of any missed dose significantly decreased (13.8% vs. 8.2% [OR, 0.56; 95% CI, 0.48, 0.64]) between the pre-post intervention periods. Patient refusal was the most frequent reason for missed doses. In the post-intervention period, patient refusal significantly decreased from 8.8% to 5.0% (OR, 0.54; 95% CI, 0.46, 0.64). Similarly, other reasons for missed doses significantly decreased from 5.0% to 3.2% (OR, 0.62; 95% CI, 0.51, 0.77). Conclusions: A real-time alert-triggered patient-centered education bundle developed and tested in an academic hospital, significantly reduced missed doses of prescribed pharmacologic VTE prophylaxis when disseminated to a community hospital.